Evaluation method of physical health course learning effect based on self-learning framework - Wang, Yan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The current evaluation method of course learning effect selects evaluation indexes through scale, which leads to too many subjective factors in the evaluation index system, large evaluation deviation and poor reliability. According to the current teaching requirements and objectives of the physical education and health course, combined with the actual learning situation of the course, and in view of the problems existing with the traditional evaluation methods, the study of physical education and health course learning effect evaluation method based on self-learning framework. The evaluation index system is established by analyzing the factors that affect the learning effect of students' physical health course. Using decision with the experimental and analytic hierarchy process (AHP) to determine index weight, using neural network structures, self-learning framework, the implementation of curriculum study effect evaluation. The results of the case study show that the students' physical fitness, sports ability and health knowledge are improved obviously after the application of the method, and the method is feasible in practice.